Perception of teachers and pupils on the influence of textbook provision on educational development in South-Western Nigeria (2010)
This study assesses the relevance of textbooks in educational development in secondary schools, determines the effect of textbooks on the performance of pupils in secondary schools and assesses the level of satisfaction of both teachers and pupils with the quality of textbooks available for their use. Based on questionnaire survey from a sample of senior secondary schools students and senior secondary school teachers the results show that both pupils and teachers ascertained the relevance of textbooks in teaching and learning and in the educational development in secondary schools. However, the results further show that textbooks are not readily available to both students and teachers. Also, both the pupils and teachers were not satisfied with the quality of textbooks available for their use. The study recommends an improvement on the quality of books coming out from the Nigerian book publishing industry, a reduction in the high cost of textbooks, provision of subsidy and tax free to book publishers on some major inputs of book publishing to ensure that the books get to the market at reasonable prices. Also, it was recommended that book publishers should increase their production level to ensure availability of textbooks in the market